A Model of Determining the Closest Point of Approach Between Ships on the Open Sea - Vujičić, Srđan; Mohović, Đani; Mohović, Robert (Promet - Traffic&Transportation, 2017)
The main objective of this paper proposes the model for the decision-making process with the intent of optimising the collision avoidance in the crossing situation on the open sea. Using the IMO Resolution standards for ship manoeuvrability, along with the equation for determining the required distance of the closest point of approach (CPA) and other parameters for own ship and the target ship, it can be possible to determine the distance at which to start alternation and collision avoidance. The research results that involved ship officers and captains with the aim of determining the Closest Point of Approach (CPA) showed a very subjective assessment method. The presented model obtained by the simulation method to determine the CPA between ships on the open sea is the key finding of this research and leaves room for further research and its further implementation on unmanned ships.